Space and Matter in the Poetic and Artistic Perception of José Ángel Valente - Ching Yu Lin (Castilla: Estudios de Literatura, 2015)
The poetry of José Ángel Valente brings up fundamental issues of space and matter, combining the poetic voice with the artistic and philosophical thought. It reveals the sense of forms of arc and circle that correspond to the wisdom of Taoism and Zen. Valente composed some poems that responded to the concept of matter represented by Spanish artists, such as Eduardo Chillida, Luis Fernández and Antoni Tàpies. Furthermore, from an ethical perspective, in the poem “Hibakusha”, Valente´s matter offers audio experiences which indicate a space of historical memory and representation of human beings. We are invited to listen to the material and corporal space ruined by atomic bombs.